Chronic renal disease among lead-exposed workers. (22nd March 2020) - Steenland, Kyle; Barry, Vaughn
Abstract : Background: Very high exposure to inorganic lead causes serious kidney damage. We have studied workers with occupational exposure and data on blood lead. Methods: We extended follow-up for 7 more years, for a previously studied cohort of 58 307 male workers who were part of a surveillance programme in 11 different states. Mortality was assessed using the National Death Index, and end-stage renal disease (ESRD) incidence was assessed using the US Renal Data System. We conducted internal analyses via Cox regression adjusting for age, calendar time and race. Results: The cohort was followed for a median of 18 years and had 524 cases of ESRD and 6527 deaths. Average maximum blood lead was 26 µg/dL; the mean year of first blood lead test was 1997. No trends by lead level were seen overall or when restricting to those with 15+ years follow-up. Among non-Caucasians with >15 years of follow-up, there was a positive but inconsistent trend (Rate ratios (RRs) 1.00, 2.10, 1.33, 2.20 and 2.76 for maximum blood lead categories of <20 µg/dL, 20–29 µg/dL, 30 to <40 µg/dL, 40 to ≤50 µg/dL and >50 µg/dL, respectively (p for linear trend 0.26). Those with >15 years of follow-up and birth year <1941 showed a positive trend with increased blood lead (RRs 1.00, 1.14, 1.18, 1.46, 1.66, p trend=0.26). Conclusions: We found no association between higher lead exposure and ESRD. There were positive but not statistically significant trends of increased risk for non-Caucasians with >15 years of follow-up and for older men with >15 years of follow-up.